Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 452 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Aspidosperma polyneuron Müll.Arg.", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 452 records from 44 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006385-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences